2023
DOI: 10.1007/s11159-023-09990-0
|View full text |Cite
|
Sign up to set email alerts
|

Translanguaging as bona fide practice in a multilingual South African science classroom

Abstract: The call for improving students’ academic achievement in science education has increased in urgency in recent years. It has also increased in complexity in the face of the growing cultural and linguistic diversity of present-day classrooms following inter- and intra-state migration. Although translanguaging pedagogy, where languages of input and output are deliberately interchanged, remains a relatively young field of research, it has grown substantially in the past decade. The study presented in this article … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…These issues have plagued the learning and uptake of STEM subjects by learners whose home language is not English [17]. Proponents of translanguaging [34,35] implore STEM, teachers to challenge learners to draw on their linguistic repertoire for meaning-making in the classroom.…”
Section: Discussionmentioning
confidence: 99%
“…These issues have plagued the learning and uptake of STEM subjects by learners whose home language is not English [17]. Proponents of translanguaging [34,35] implore STEM, teachers to challenge learners to draw on their linguistic repertoire for meaning-making in the classroom.…”
Section: Discussionmentioning
confidence: 99%
“…When the focus is on primary school teachers, the number of studies found in the search decreases, as well as when the focus is on language teaching. However, multilingualism is sometimes considered from the perspective of other subjects [43]. Some studies focus on additional language didactics, sometimes in specific countries [32][33][34][35][36][37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…Three articles deal with the teaching of additional languages: One on the language policy applied by the Belgian government regarding the task-based methodology for teaching Flemish [40]; in another article, Fhonna and Yusuf [41] analyze the methodologies applied in Australia for the didactics of Indonesian as an additional language; and a study in Seychelles evaluates the quality of learners' written productions according to the language in which they write about their knowledge [42]. Finally, regarding language acquisition through content, Charamba [43] evaluates the process of translingualism as a good practice for a multilingual science classroom in South Africa. Focusing on multilingualism versus monolingualism, [44] reports on the perceptions and differences of each type of learner when acquiring an additional language.…”
Section: State Of the Artmentioning
confidence: 99%
“…Learners who move frequently may also have gaps in their education, which can affect their ability to acquire new knowledge and skills, including language proficiency (Hanna, 2022;Neluvhola et al, 2022). This is compounded in instances, where there is low teacher turnover, no further training of teachers, and a lack of continuity in language instruction (Cekiso et al, 2019;Charamba, 2023).…”
Section: Learner Mobilitymentioning
confidence: 99%